2024
DOI: 10.1371/journal.pone.0297393
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between climate change, globalization and non-communicable diseases in Africa: A systematic review

Alhassan Siiba,
Joseph Kangmennaang,
Leonard Baatiema
et al.

Abstract: Climate change and non-communicable diseases (NCDs) are considered the 21st Century’s major health and development challenges. Both pose a disproportionate burden on low- and middle-income countries that are unprepared to cope with their synergistic effects. These two challenges pose risks for achieving many of the sustainable development goals (SDGs) and are both impacted by globalization through different pathways. While there are important insights on how climate change and or globalization impact NCDs in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“…Siiba et al. 11 in a systematic review found that extremes of weather from drought to flooding disrupt healthcare for people living with cancer, diabetes, and cardiovascular disease. These patients were at risk of exacerbation of health problems following such disasters because of interruptions with their treatment, problems with drug supplies chains, or inability to access healthcare due transport disruptions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Siiba et al. 11 in a systematic review found that extremes of weather from drought to flooding disrupt healthcare for people living with cancer, diabetes, and cardiovascular disease. These patients were at risk of exacerbation of health problems following such disasters because of interruptions with their treatment, problems with drug supplies chains, or inability to access healthcare due transport disruptions.…”
mentioning
confidence: 99%
“…These patients were at risk of exacerbation of health problems following such disasters because of interruptions with their treatment, problems with drug supplies chains, or inability to access healthcare due transport disruptions. 11 Mitigating the devastating impact of climate change on human development is way beyond the health system yet the resultant disease, suffering and deaths are a medical problem.…”
mentioning
confidence: 99%